Disfungsi Organisasi Dagang di Luar Negeri Sebagai Aktor Diplomasi Indonesia - Rino F. Boer; Jessica Wongsodiharjo (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2019)
The existence of organizations that fight for the interests of Indonesia abroad is often only associated with the Indonesian Embassy (Indonesian Embassy). There are international trade organizations that play an important role in diplomacy such as the INTCC in Bangkok. INTCC held various activities aimed at assisting the promotion of the investment climate in Indonesia to local entrepreneurs through various trade diplomacy meetings, seminars, workshops, business forums, investment exhibitions, to sports competitions. However, in reality, INTCC did not succeed in getting full support from its stakeholders in Bangkok. The research objective is to identify the factors that cause the disfunction of this trade organization as an Indonesian diplomacy actor by using fully functioning society theory. This study uses a qualitative approach with a case study method that uses in-depth interviews with informants. Failure to maintain balance in accommodating all the interests of stakeholders, social capital that fails to form, and weaknesses in the use of language are the main factors causing this failure. The formation of full support from the local community is a key factor in the success of diplomatic actors, especially those from non-government official actors. The benefits of the research are expected to be able to develop studies on the engagement process quickly, accurately and efficiently to encourage the role of organizations abroad so that they can run more optimally to produce the expected output.